THE COMPARISON OF TWO TEST ITEM FORMATS IN ASSESSING STUDENTS’ READING COMPREHENSION ABILITY - Fidalia MR (STKIP Siliwangi, 2014)
This study discussed the comparison of the two kinds of test in assessing students’ reading comprehension skill. The sample of this research was 36 eighth grade students in one of the SMP-s in Riau. It employed quantitative research. The data collection technique used was reading comprehension test. Furthermore, the data obtained from both test item formats were analyzed, compared and calculated in form of paired samples t-test analysis by using IBM SPSS statistics version 22. The research findings showed some points; there are 4.5833 point differences between two mean scores result (short answer and multiple choice test), the correlation between the result of the two test item formats is .626 which means that there is high correlation between them, and based on the comparison of t value and t table and the P value, it was found H0 is accepted which means that there is no effect of the use of those two test item formats in students’ score in assessing students’ reading comprehension ability. Keywords: comparison, testing, multiple choice, short answer, reading comprehension